DEVELOPMENT OF SELF-ASSESSMENT OF CHILDREN OF PRESCHOOL AGE - Yusupova, Muhabbar (Журнал иностранных языков и лингвистики, 2021)
In the process of socialization, a person gradually acquires self-awareness and develops his self-esteem. Within the framework of the study of self-awareness, self-esteem is assigned a leading role, which is why the topic of the formation of self-esteem of a person in preschool age is extremely relevant today. Self-esteem is the most important element of the personality of a person, which largely determines the foundations of life of a person, the level of his aspirations, as well as the entire system of intrapersonal judgments. It determines the dynamics and direction of the development of the subject.